Euphemistic Expression in Indonesian Obituaries - Jaganegara, Haidar; Wijana, I Dewa Putu (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2023)
Euphemisms are common in obituaries because a written announcement of someone's death has a touchy topic. In the case of obituaries, people mostly use feelings to avoid using hurtful words to give good effect to society in conveying or announcing someone's death in an effort to minimize any negative societal impact. Thus, the study aims to analyze the euphemism expression in written data obtained from the Indonesian obituaries and take into account the types and functions. The research data in this study consists of the euphemism expression; words, phrases, and clauses in Tempo (January–July 2021), Detik.com, and Kompas (July–December 2021) online obituaries. The qualitative method was used and descriptive tables including frequencies and percentages were shown. As a result, in Indonesian obituaries, the following euphemism expressions were found in the types: (1) metaphor (14.34%), (2) one-for-one substitution (34.73%), (3) abbreviation (1.80%), (4) acronym (1.20%), (5) using pronoun (7.78%), (6) general for specific (1.20%), (7) circumlocution (6.58%), (8) hyperbole (8.98%), (9) understatement (3.60%), and (10) borrowing (19.76%). The highest frequency of the euphemism types is one-for-one substitution. It is found in 58 instances out of 167 of the total data, or 34.73%. Thus, it is concluded that Indonesian obituaries often replace the term related to the death, which has a hurtful connotation with the softer expression that has relationships in its meaning component. In addition, euphemisms also served a number of functions in Indonesian obituaries, including (1) the protective (12.57%), (2) the underhand (36.52%), (3) the uplift (5.98%), (4) the provocative (33.55%), (5) the cohesive (9.58%), and (6) the ludic (1.80%). The euphemism function of the underhand is dominated in the findings with 61 instances or 36.52%, so it conveys that Indonesian obituaries often blur the sensitiveness by not using the direct term.